Antioxidant Activity of Edible Film Made From Catfish (Pangasius hypophthalmus) Gelatin Supplemented With Astaxanthin Using DPPH Method - Nasution, Azlaini Yus; Wahyuni, Intan Sri (JURNAL PROTEKSI KESEHATAN, 2023)
Edible film is a food packaging material that can be consumed along with the packaged product. In this study, the edible film was made from catfish gelatin and supplemented with astaxanthin, which possesses antioxidant activity. The objective of this research was to determine the antioxidant activity of catfish gelatin edible film supplemented with 0.5% astaxanthin and compared with comparative film. The antioxidant activity was measured using the DPPH method with a microplate reader at five concentrations of sample 62.5 mcg/ml, 125 mcg/ml, 250 mcg/ml, 500 mcg/ml, and 1000 mcg/ml. The results of the antioxidant activity test showed that the IC50 value of the edible film supplemented with astaxanthin was 251.06x103 mcg/ml, while the comparative edible film was 133.12 mcg/ml. In conclusion, the edible film supplemented with astaxanthin exhibited weaker antioxidant activity compared to the comparative film.